Detectionof gas hydrates infaults using azimuthal seismic velocity analysis,Vestnesa Ridge, W-Svalbard Margin - Singhroha, Sunny; Bünz, Stefan; Plaza-Faverola, Andreia; Chand, Shyam (Journal of Geophysical Research: Solid Earth, 2020)
Accepted for publication in Journal of Geophysical Research. Solid Earth. Copyright 2020 American Geophysical Union. Further reproduction or electronic distribution is not permitted. Joint analysis of electrical resistivity and seismic velocity data is primarily used to detect the presence of gas hydrate‐filled faults and fractures. In this study, we present a novel approach to infer the occurrence of structurally‐controlled gas hydrate accumulations using azimuthal seismic velocity analysis. We perform this analysis using ocean‐bottom seismic (OBS) data at two sites on Vestnesa Ridge, W‐Svalbard Margin. Previous geophysical studies inferred the presence of gas hydrates at shallow depths (up to ~190‐195 m below the seafloor) in marine sediments of Vestnesa Ridge. We analyze azimuthal P‐wave seismic velocities in relation with steeply‐dipping near surface faults to study structural controls on gas hydrate distribution. This unique analysis documents directional changes in seismic velocities along and across faults. P‐wave velocities are elevated and reduced by ~0.06‐0.08 km/s in azimuths where the raypath plane lies along the fault plane in the gas hydrate stability zone (GHSZ) and below the base of the GHSZ, respectively. The resulting velocities can be explained with the presence of gas hydrate‐ and free gas‐filled faults above and below the base of the GHSZ, respectively. Moreover, the occurrence of elevated and reduced (>0.05 km/s) seismic velocities in groups of azimuths bounded by faults, suggests compartmentalization of gas hydrates and free gas by fault planes. Results from gas hydrate saturation modelling suggest that these observed changes in seismic velocities with azimuth can be due to gas hydrate saturated faults of thickness greater than 20 cm and considerably smaller than 300 cm.